What is lean 4.0? / Azyyati Anuar and Daing Maruak Sadek - Anuar, Azyyati; Maruak Sadek, Daing (Faculty of Business and Management, Universiti Teknologi MARA Cawangan Kedah, 2022)
The fundamental concept of waste reduction and efficiency enhancement, which started with Japanese automobile manufacturing, has existed for an extended time. This occurred even before the term lean was introduced by John Krafcik in 1988 (Laaper & Kiefer, 2020). Currently, the manufacturing industry is undergoing a gradual transformation from craft to mass production and from mass to lean production. Lean production is an approach that continues to succeed by reducing industry complexity. However, the complexity has increased as a result of the intricacy of market demands, an unbalanced environment and excessively ambitious customers (Cifone & Staudacher, 2021). In this regard, lean applications are unlikely to be feasible in the industry as the production processes become more challenging in tandem with technological advancements. Therefore, a new research topic, Industry 4.0 (IR4.0) comes into place to deal with the increased production complexity (Mayr et al., 2018). In this sense, the introduction of Lean 4.0 and its integration with IR4.0 could be viewed as a revitalized version of lean (Raji et al., 2021). Though it is believed that Lean 4.0 will contribute to robust production, by far, there is no universally accepted definition of Lean 4.0, and its components have not yet existed (Rybski & Jochem, 2021).